2010
DOI: 10.1007/s11569-010-0090-y
|View full text |Cite
|
Sign up to set email alerts
|

Sunscreens with Titanium Dioxide (TiO2) Nano-Particles: A Societal Experiment

Abstract: The risks of novel technologies, such as nano(bio)technology cannot be fully assessed due to the existing uncertainties surrounding their introduction into society. Consequently, the introduction of innovative technologies can be conceptualised as a societal experiment, which is a helpful approach to evaluate moral acceptability. This approach is illustrated with the marketing of sunscreens containing nano-sized titanium dioxide (TiO2) particles. We argue that the marketing of this TiO2 nanomaterial in UV prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
71
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(75 citation statements)
references
References 21 publications
1
71
0
1
Order By: Relevance
“…The images also revealed that most Np had elliptical morphology with a smooth surface ( Figure 3B). These results corroborate the observations of Jacobs and coworkers [24] who noticed that TiO 2 -Np tend to agglomerate and aggregate into larger structures. Thus, to refer to TiO 2 -Np as monodisperse may be a misnomer under common environmental conditions [25].…”
Section: Resultssupporting
confidence: 92%
“…The images also revealed that most Np had elliptical morphology with a smooth surface ( Figure 3B). These results corroborate the observations of Jacobs and coworkers [24] who noticed that TiO 2 -Np tend to agglomerate and aggregate into larger structures. Thus, to refer to TiO 2 -Np as monodisperse may be a misnomer under common environmental conditions [25].…”
Section: Resultssupporting
confidence: 92%
“…3, 349-351, http Van de Poel (2011) argues that nuclear power should be treated as an ongoing social experiment that needs to be continuously monitored and evaluated. In his reports (2009; Jacobs, Van de Poel, & Osseweijer, 2010), he makes similar claims about other technologies. Van de Poel's main point is that the technology-as-a-social-experiment metaphor has important implications for the ethical evaluation of new technologies.…”
Section: Please Scroll Down For Articlementioning
confidence: 94%
“…The nanoparticles can, for example, be fixed in a matrix, such as the silica beads with nano-sized TiO 2 particles from the Sunjin Chemical Corporation, or be bonded together via a surface coating. 126 The presence of coatings also adds to the uncertainty about the effectiveness of efforts to reduce unwanted photo activity, and the durability of the coating layer during its life-cycle. 128 Some researchers have characterized silica, zircon and alumina as charge transfer catalysts, 129 which are solids that have the ability to trap reactive electrons (e − ) and electropositive holes (h + ), 130 and their porous structures facilitate the access of reactant molecules to active surface sites.…”
Section: Surface Coatingsmentioning
confidence: 99%
“…The labels on sunscreens generally do not indicate which crystal forms of titanium dioxide are present or what types of coating are used. The material used for the surface coatings, its thickness, its chemical purity, or the use of multiple coatings further increases the heterogeneity of the utilized TiO 2 nanoparticles, 126,127 The matrix in which the nano-sized TiO 2 particle resides contributes another factor. The nanoparticles can, for example, be fixed in a matrix, such as the silica beads with nano-sized TiO 2 particles from the Sunjin Chemical Corporation, or be bonded together via a surface coating.…”
mentioning
confidence: 99%